LIM-Domain-Binding Protein 1 Mediates Cell Proliferation and Drug Resistance in Colorectal Cancer - Zhu, Mo; Jiang, Baofei; Zuo, Hao; Wang, Xiaopeng; Ge, Hengfa; Huang, Ziming (Frontiers in Surgery, 2022)
Objective: It has been shown that LIM-domain-binding protein 1 (LDB1) is involved in the tumorigenesis of several cancers, but its function in colorectal cancer (CRC) has not been fully explained. This study is aimed to investigate whether LDB1 involves in regulating the cell growth and drug sensitivity of CRC. Methods: Western blot was used to analyze the protein expression of LDB1 in CRC tissues. KM plotter database and UALCAN were used to predict the prognosis of CRC patients with low or high LDB1 expression. GEPIA database was used to do the correlation analysis in CRC tissues. CCK-8 assay and xenograft models were used to evaluate the effects of LDB1 in CRC cell growth. A oxaliplatin-resistant cell line was constructed to evaluate the effect of LDB1 in drug sensitivity of CRC cells. Results: Our current research confirmed that LDB1 was up-regulated in CRC tumor tissues, and predicted a poor prognosis for CRC patients. LDB1 was also found positively correlated with CCNA1, BCL2 and BCLW, but negatively correlated with the pro-apoptotic signals (BID, BAX and BAK). Silence of LDB1 significantly inhibited CRC cell growth in vitro, and CRC cells with low expression of LDB1 had a low tumorigenesis rate in tumor-bearing nude mice. Our experiments also showed that LDB1 silence enhanced the anti-tumor activity of oxaliplatin in CRC cells. LDB1 was also found elevated in oxaliplatin-resistant CRC cells, and silence of LDB1 partly restored the antitumor effect of oxaliplatin in oxaliplatin-resistant CRC cells. Conclusion: Our current results revealed the roles of LDB1 in the growth and drug resistance of CRC cells, and may provide the new theoretical support for LDB1 as a potential target for the treatment of CRC in the future.